VOx/SiO2 Catalyst Prepared by Grafting VOCl3 on Silica for Oxidative Dehydrogenation of Propane. Issue 20 (7th September 2015) - Zhu, Haibo; Ould‐Chikh, Samy; Dong, Hailin; Llorens, Isabelle; Saih, Youssef; Anjum, Dalaver H.; Hazemann, Jean‐Louis; Basset, Jean‐Marie
Abstract The VOx/SiO2 catalysts for oxidative dehydrogenation of propane were synthesized by a simple grafting method. The VOCl3 was first grafted at the surface of SiO2, which was dehydrated at different temperature (from 200 to 1000 °C). The formed grafted complexes were then calcined in air, leading to the formation of VOx/SiO2 catalysts. The synthesized catalysts were characterized by nitrogen adsorption, SEM, Raman spectroscopy, temperature‐programmed reduction, and extended X‐ray absorption fine structure analysis. The SiO2 pretreatment temperature has an evident effect on the loading and dispersion of VOx on SiO2, which finally affects their catalytic performance. High SiO2 treatment temperature is beneficial to dispersing the vanadium oxide species at the SiO2 surface. These materials are efficient catalysts for the catalytic oxidative dehydrogenation of propane to propylene. The best selectivity to propylene is achieved on the VOx/SiO2‐(1000) catalyst. The high selectivity and activity are well maintained for three days catalytic reaction.